Immunochromatography in CSF improves data on surveillance of S. pneumoniae meningitis in India - Yuvaraj Jayaraman; Sanjay Mehendale; Ranjith Jayaraman; Rosemol Varghese; Girish K. Chethrapilly Purushothaman; Prabu Rajkumar; Bharathy Sukumar; Rajamohanan K. Pillai; Girija Mohan; Devasena N. Radhakrishnan; Sujatha Sridharan; Narayan Babu; et al. (Elsevier, 2018)
Introduction: Streptococcus pneumoniae is a significant cause of childhood bacterial meningitis in India. The United States Food and Drug Administration has licensed an immunochromatographic (ICT) test, Binax®NOW™, to detect the C polysaccharide antigen of S. pneumoniae in cerebrospinal fluids (CSF). Accurate etiological diagnosis of bacterial meningitis in India is essential for effective treatment strategies and preventive interventions. Materials and methods: CSF samples from 2081 children admitted, with clinically suspected bacterial meningitis at 11 sentinel sites of hospital based sentinel surveillance network for bacterial meningitis in India between September 2009 and December 2016 were tested with ICT. Concurrent CSF cultures were processed using standard procedures. Results and discussion: S. pneumoniae was detected thrice the number of times by ICT than by CSF culture, with a sensitivity and specificity of 100% and 95.3% respectively. This rapid ICT test proves to be of immense use as a diagnostic test for meningitis patients with/without prior antibiotic treatment, especially in facilities with limited laboratory infrastructure in resource limited settings. Keywords: India, Pneumococcal meningitis, Binax, Rapid test